The Analysis Study of Cell Adhesion Molecules and Estrogen Receptor Expression In The Endometrium of Patients With Polycystic Ovary Syndrome: A Comprehensive Systematic Review - Ida Bagus Agung , Brahmananda Krisna Putra; I Gede , Sudiarta; Putu, Ayu Novianitri; I kadek, Pramarta; I Nym Gde, Dwipa Mahardikha; I Komang, Juni Arthawan; Adisastra, Suryantha; AA Gde , Marvy Khrisna Pranamartha (The International Journal of Medical Science and Health Research, 2024)
Introduction: Polycystic Ovary Syndrome (PCOS) is a multifaceted endocrine disorder affecting up to 7% of women in their reproductive years. Research on estrogen receptor expression and cell adhesion molecules in the endometrium is increasing, focusing on their roles in endometrial growth and embryo implantation. Despite insights, studies investigating these endometrial changes in PCOS are limited. Methods: This systematic review follows the PRISMA 2020 guidelines to analyze the relationship between cell adhesion molecules, estrogen receptor expression, and endometrial characteristics in patients with PCOS. Results: Eight relevant publications were identified after thorough screening from reputable sources. The included studies contribute to understanding the association between estrogen receptor gene variants and PCOS through various research approaches, highlighting significant findings related to estrogen receptor expression, cellular adhesion markers, and their implications on fertility. Conclusion: Variations in ESR1 and ESR2 gene SNPs are associated with altered protein structures that may contribute to PCOS pathogenesis. Genetic and molecular mechanisms identified in this review indicate how these variations can influence PCOS phenotypes and highlight the need for further research to develop targeted therapies.